TINJAUAN STRATEGI PEMASARAN PARIWISATA AIR TERJUN TAENO DI NEGERI RUMAH TIGA, KECAMATAN TELUK AMBON - Adelliyan Adelliyan; Abdul Haris Tamalene (Jurnal Administrasi Terapan, 2026)
Taeno Waterfall is a natural tourist attraction located in Taeno Upper Hamlet, Negeri Rumah Tiga, Teluk Ambon District. Although it has an attractive appeal and beautiful scenery, the number of tourists visiting Taeno Waterfall is still relatively low. This is due to the lack of marketing strategies used by the local government of Negeri Rumah Tiga and the managers to introduce Taeno Waterfall to the wider public. This study aims to determine the tourism marketing strategies for Taeno Waterfall in Negeri Rumah Tiga, Teluk Ambon District. The method used in this writing is qualitative data analysis, in which data are obtained descriptively using the service marketing mix analysis tool. The result of this study is to provide input and solutions on the tourism service marketing strategy for Taeno Waterfall, so that it can increase visitors’ interest in visiting Taeno Waterfall. This study concludes that Taeno Waterfall has not implemented the right marketing strategy to attract visitors, resulting in a continual decline in tourist visits. To address this, management should understand marketing strategies by referring to the Service Marketing Mix (product, price, place, promotion, people, process, physical evidence) to increase tourists' interest in visiting Taeno Waterfall in Negeri Rumah Tiga, Teluk Ambon District. Keywords: Tourism Marketing Strategy